2021
DOI: 10.1016/j.crphar.2021.100069
|View full text |Cite
|
Sign up to set email alerts
|

Secretome effect of adipose tissue-derived stem cells cultured two-dimensionally and three-dimensionally in mice with streptozocin induced type 1 diabetes

Abstract: Aims To analyze therapeutic potential of the conditioned medium from adipose tissue-derived stem cells (ASC) cultivated in 2D (CM-2D) and 3D (CM-3D) models, in mice with Type 1 diabetes (T1D) induced by streptozotocin. Main methods Viability andCD105 expression of 2D and 3D ASC were analyzed by flow cytometry. T1D was induced in mice by multiple injections of streptozocin. On the 28th and 29th days after the first injection of streptozocin, diabetic animals received CM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Male Swiss mice obtained from Charles River Laboratories (L’arbresle, France) were housed at constant temperature (20–22°C) and with a 12-h light–dark cycle. At the age of 2 mo, they received an intraperitoneal injection of STZ (40 mg/kg) diluted in citrate buffer (0.05 mmol/L, pH 4.5) for four consecutive days, as described previously[ 21 ]. A week later, mice receiving only citrate buffer (nondiabetic) and treated mice exhibiting blood glucose ≥ 300 mg/100 mL (STZ diabetic) were subdivided into four groups of eight males, with either free access to water (control) or a 0.5% Bza solution as drinking liquid (Bza-drinking) for 24 d. To measure plasma insulin levels at the beginning of treatment, blood samples were withdrawn from tail vein then centrifuged and analyzed using Ultrasensitive insulin-ELISA kit (Mercodia, Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Male Swiss mice obtained from Charles River Laboratories (L’arbresle, France) were housed at constant temperature (20–22°C) and with a 12-h light–dark cycle. At the age of 2 mo, they received an intraperitoneal injection of STZ (40 mg/kg) diluted in citrate buffer (0.05 mmol/L, pH 4.5) for four consecutive days, as described previously[ 21 ]. A week later, mice receiving only citrate buffer (nondiabetic) and treated mice exhibiting blood glucose ≥ 300 mg/100 mL (STZ diabetic) were subdivided into four groups of eight males, with either free access to water (control) or a 0.5% Bza solution as drinking liquid (Bza-drinking) for 24 d. To measure plasma insulin levels at the beginning of treatment, blood samples were withdrawn from tail vein then centrifuged and analyzed using Ultrasensitive insulin-ELISA kit (Mercodia, Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, diabetic phenotypes of diverse animal models have been ameliorated when white adipose tissue (WAT) or brown adipose tissue (BAT) has been reintroduced in these models, irrespective of the method used. Nowadays, it is suggested that adipose tissue contributes to the correction of type 1 diabetes, since hyperglycemia was lowered in diabetic mice treated by conditioned media from adipose-derived stem cells[ 21 ], and since mitigation of diabetes was observed in STZ diabetic mice receiving BAT transplantation[ 19 ]. To date, the beneficial effects of ingested Bza on glucose and lipid handling have been studied in obese rodents only[ 1 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pdx1, a β‐cell marker, was increased in the 2D‐CM group, but this effect was not seen in the 3D‐CM. [ 107 ] In our previous study, content analysis was performed on CMs produced with UC‐MSCs cultured in 2D and 3D environments before examining their in vivo therapeutic effects. Scaffolds were used for the 3D culture, and the cells were grown following a specific topography.…”
Section: Therapeutic Effects Of Msc‐cm On Diabetes and Related Compli...mentioning
confidence: 99%
“…Here we aimed to compare the secretomes of AT-MSCs, BM-MSCs, gingiva-derived MSCs (G-MSCs), placenta-derived MSCs (PL-MSCs), and umbilical cord-derived MSCs (UC-MSCs) cultured as monolayers (2D) and as cell spheroids (3D), since there is evidence that culturing conditions also have an impact on the cells' secretome 22 . We have analyzed the expression of 41 cytokines and growth factors in the CM samples taken on the 3rd day of culturing and assessed the MSCs-derived CM effect on macrophages polarization in vitro.…”
Section: Introductionmentioning
confidence: 99%